The psichological peculiarity structure organization of pupils and students - N P Kirina (Peoples' Friendship University of Russia (RUDN University), 2009)
The article considers age differences of the psychological structure of pupils and students organization baseol on the general-functional approach to studying the qualities of the personality, which gives an opportunity to study age pecularities of organization in detail.